PERBANDINGAN PENGARUH ANTARA PENDEKATAN SAVI DAN PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS - Melati, Stella Riski; Aeni, Ani Nur; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
This study aims to improve mathematical communication abilities on plane figures chapter for five grade students at SDN 3 Arjawinangun and SDN 1 Arjawinangun by using Somatic, Auditory, Visual and Intellectual (SAVI) technique and contextual technique. The study was conducted during nine meetings with three meetings for each class. To measure the ability of students’ mathematical communication, some data were collected such as documents, observation sheets, test results and documentation. Based on the results can be obtained that the ability of students’ mathematical communication used SAVI method and contextual method increased. This conclusion is also showed by teacher performance observation sheets and student activities in the class. In the SAVI method and contextual method can improve the ability of mathematical communication and cultivate a sense of fun for students and improve the students activities at learning process.